2021
DOI: 10.1088/1361-648x/ac2203
|View full text |Cite
|
Sign up to set email alerts
|

First principles studies of the electronic and structural properties of the rutile VO2(110) surface and its oxygen-rich terminations

Abstract: We present a density functional theory (DFT) study of the structural and electronic properties of the bare metallic rutile VO2 (110) surface and its oxygen-rich terminations. Due to the polyvalent nature of vanadium and abundance of oxide phases, the modelling of this material on the DFT level remains a challenging task. We discuss the performance of various DFT functionals, including PBE, PBE + U (U = 2 eV), SCAN and SCAN + rVV functionals with non-magnetic and ferromagnetic spin ordering, and show that the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…One of the most notable differences between spin-polarized and non-spin-polarized calculations for surface free energies is in the absolute values of the effective adsorption energies. 59 For instance, the results from Ref. 59 revealed that the non-magnetic PBE oxygen adsorption energy on the VO 2 (110) surface is À1.88 eV, and spin-polarized calculations shift this value by 0.20 eV to the right (less negative value).…”
Section: Heterostructurementioning
confidence: 99%
“…One of the most notable differences between spin-polarized and non-spin-polarized calculations for surface free energies is in the absolute values of the effective adsorption energies. 59 For instance, the results from Ref. 59 revealed that the non-magnetic PBE oxygen adsorption energy on the VO 2 (110) surface is À1.88 eV, and spin-polarized calculations shift this value by 0.20 eV to the right (less negative value).…”
Section: Heterostructurementioning
confidence: 99%